Effects of brand extension on the updated hotel brand personality and attitude toward the brand - Ryu, Hyungseo (Kansas State University, 2006)
The objective of this research is to identify how different types of brand personalities affect brand extension and to then address what the most appropriate brand extension types for hotel brands are. This offers a better position to assess the broader impact of extension strategy for the marketer. The methodology for achieving these objectives are described in the following sections: developing measurements based on extensive reviews of literature; conducting a pretest with 15 graduate students and faculty members; establishing validity and reliability of the instrument through a pilot test; modifying brand personality measurement items based on the descriptive analysis and exploratory factor analysis of the pilot test; collecting data from students and faculty members at a Midwestern university and residents in Midwestern and Southern area; and analyzing data used a exploratory factor analysis, t -tests and a series of simple linier regression analyses. Descriptive analyses were performed on all attributes of brand personality, customer personality, brand personality congruence and extended brand personality and updated brand congruence in the questionnaire. The results of this study showed customer's brand congruence have a greater impact on the customers' positive attitude toward core brand. However, customers' attitude toward core brand had no impact on the updated attitude. The findings provide some theoretical and practical implications for hotel operators. The results of the present study suggest that hotel marketers should develop marketing information systems that continuously monitor hotel customers' perceptions of hotel brand image.